EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH - Agus Setiawan; Nurdin Arsyad (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to determine the effectiveness of implementing an index card match type of active learning strategy in mathematics learning. This type of research is a pre-experimental study involving one class as an experimental class. This study refers to three criteria for the effectiveness of learning, namely student mathematics learning outcomes, student activity during the mathematics learning process and student responses to mathematics learning through active learning strategies type index card match. Data analysis using analysis descriptive and t-test with a significance level of α = 5%. The results showed that the average posttest score of students' mathematics learning outcomes through active learning strategies type index card match was 85.96 with a standard deviation of 6.37 with an ideal score of 100, from these results that 30 students or 93.75% had achieved completeness. individual and this means that classical completeness has been achieved, descriptively the normalized gain obtained is 0.69 (in the medium category) and inferential with a significance level of 5% is also said to be fulfilled, descriptively the classical completeness achieved is 93.75% greater than the specified criteria, namely 75%, inferential with a significance level of 5% is also declared fulfilled. The average percentage of student activity frequency for each indicator reaches the effective criteria, namely 81.73%. The student response questionnaire which shows that the student's response to the active learning strategy type index card match is 86.97%. From the results of this study, it can be concluded that the active learning strategy type index card match is effectively applied in mathematics learning in class VIII students of SMP Negeri 2 Sungguminasa, Gowa Regency. Keywords: Effectiveness, active learning strategies, Index card match